MENINGKATKAN MUTU PENDIDIKAN KARAKTER SISWA MELALUI PENERAPAN TRI HITA KARANA DI SEKOLAH DASAR - Komang Citra Padma Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Every human being needs a safe, peaceful and peaceful life. This will be possible if everyone is able to look after each other. Maintaining a harmonious relationship with God, maintaining a harmonious relationship with fellow humans and a harmonious relationship with the natural environment is important to do as early as possible, considering the negative impact of technological developments that cannot be avoided. Tri Hita Karana is a Balinese Hindu philosophy that includes three main relationships: the harmonious relationship between humans and God (Parahyangan), the harmonious relationship between humans and fellow humans (Pawongan), and the harmonious relationship between humans and the environment (Palemahan). This philosophy is an important foundation in the life of the Balinese people and has been adopted in various aspects of life, including in the field of education. This research aims to explore the quality of student character education through the application of Tri Hita Karana in elementary schools. This research uses a qualitative descriptive approach with data collection methods through observation, interviews and documentation. Observations were carried out to directly observe how activities related to Tri Hita Karana were carried out in the school environment. Interviews were conducted with students to gain an in-depth understanding of their perceptions and experiences regarding the implementation of Tri Hita Karana values. Documentation is used to review various school records, such as school work programs, activity agendas, and learning materials related to student character education